Estimating Prevalence of Hepatitis C Virus Infection in the United States, 2013‐2016. Issue 3 (6th November 2018) - Hofmeister, Megan G.; Rosenthal, Elizabeth M.; Barker, Laurie K.; Rosenberg, Eli S.; Barranco, Meredith A.; Hall, Eric W.; Edlin, Brian R.; Mermin, Jonathan; Ward, John W.; Ryerson, A. Blythe
Abstract : Hepatitis C virus (HCV) infection is the most commonly reported bloodborne infection in the United States, causing substantial morbidity and mortality and costing billions of dollars annually. To update the estimated HCV prevalence among all adults aged ≥18 years in the United States, we analyzed 2013‐2016 data from the National Health and Nutrition Examination Survey (NHANES) to estimate the prevalence of HCV in the noninstitutionalized civilian population and used a combination of literature reviews and population size estimation approaches to estimate the HCV prevalence and population sizes for four additional populations: incarcerated people, unsheltered homeless people, active‐duty military personnel, and nursing home residents. We estimated that during 2013‐2016 1.7% (95% confidence interval [CI], 1.4‐2.0%) of all adults in the United States, approximately 4.1 (3.4‐4.9) million persons, were HCV antibody‐positive (indicating past or current infection) and that 1.0% (95% CI, 0.8‐1.1%) of all adults, approximately 2.4 (2.0‐2.8) million persons, were HCV RNA–positive (indicating current infection). This includes 3.7 million noninstitutionalized civilian adults in the United States with HCV antibodies and 2.1 million with HCV RNA and an estimated 0.38 million HCV antibody‐positive persons and 0.25 million HCV RNA–positive persons not part of the 2013‐2016 NHANES sampling frame. Conclusion: Over 2 million people in the United States had current HCV infection during 2013‐2016; compared to past estimates based on similar methodology, HCV antibody prevalence may have increased, while RNA prevalence may have decreased, likely reflecting the combination of the opioid crisis, curative treatment for HCV infection, and mortality among the HCV‐infected population; efforts on multiple fronts are needed to combat the evolving HCV epidemic, including increasing capacity for and access to HCV testing, linkage to care, and cure.